Elvitegravir: an emerging HIV integrase inhibitor. (September 2008) - Shimura, Kazuya; Kodama, Eiichi
Integration of the reverse transcribed HIV dsDNA into the host cell chromosome is critical for the subsequent production of progeny virions. In October 2007, the US FDA approved the first HIV-1 integrase inhibitor, raltegravir, as a therapeutic agent for treatment-experienced HIV-1-infected patients. Elvitegravir (GS-9137) is another HIV integrase inhibitor, which has a distinct chemical structure from raltegravir, and is currently being evaluated in HIV-1-infected patients. In Phase II clinical trials, elvitegravir combined with optimized background therapies significantly reduced the plasma HIV-1 viral load without serious adverse events up to 24 weeks. This article reviews the most recent available information on elvitegravir with respect to its clinical pharmacokinetics, pharmacodynamics and drug-resistance profile, and from the standpoint of extensive in vitro studies of its broad antiretroviral activity.